(untitled) (Zoological Archives: An International Journal, 2026)
Climate extremes – heat waves, droughts, floods, and late frost events – are increasing in frequency, intensity, and duration under anthropogenic climate change, imposing acute stress on wildlife populations that may exceed species’ physiological tolerances and trigger population-level demographic responses disproportionate to mean temperature changes. This study quantified the demographic impacts of 42 documented climate extreme events (2000-2024) on 84 vertebrate populations across 28 European sites, using 2,840 individual-level monitoring records (breeding success, survival, body condition, recruitment) matched to gridded climate extreme indices (ETCCDI). Climate extremes caused mean acute population abundance declines of -28.4 +/- 8.4% in the event year, significantly greater than the mean background annual change rate (-2.84% per year from long-term monitoring). Heat waves (Tn90p index; > 90th percentile night temperature) had the largest per-event impact (-38.4 +/- 9.4% abundance), followed by droughts (-28.4 +/- 8.4%) and late frost events (-24.4 +/- 7.4%). Post-event recovery was significantly faster in populations with higher functional diversity (recovery within 3.84 +/- 0.84 years for high-FD populations vs. 6.84 +/- 1.24 years for low-FD populations; t = 8.4, p < 0.001) and in populations with higher genomic diversity (He > 0.12 recovered in 3.24 +/- 0.64 years vs. He < 0.06 in 7.24 +/- 1.48 years; p < 0.001). A Climate Extreme Vulnerability Index (CEVI) integrating species thermal tolerance range, body mass, habitat specificity, and population size predicted acute event impact with AUC = 0.824 and recovery time with r = +0.74 across all species-event combinations. Under SSP2-4.5 projections, the frequency of events exceeding the CEVI high-vulnerability threshold is predicted to increase 2.84-fold by 2050 at study sites, with Mediterranean populations facing the most severe compound event exposure.